Turnover tra generazioni nel settore agrario: il caso della mancata applicazione della misura PACSRG004 “Cooperazione per il ricambio generazionale” - Pippo Russo (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
The issue of agricultural turnover is high on the policy agenda of the European Community and political and social scientists. A structural feature of the European agricultural system, for which no solution has yet been found, is the difficult access of persons under 40 to positions of ownership and control of agricultural holdings. Although methodological simplifications tend to underestimate the real generational change in farming, the problem remains unresolved and requires appropriate responses that will encourage the fight against aging of agricultural sector. An attempt has been made to move in this direction with the CAP measure SRG004, entitled “Cooperation for generational renewal”. It provides a mechanism for the possibility of establishing cooperation between a farmer over 65 and a newcomer. A check on the implementation of SRG004 in Italy revealed: None of the Italian regions had adopted the measure. Based on this information, qualitative research was organized. The aim was to find out the reasons for this generalization. The research highlighted some of the mechanisms of implementation of multi-level agricultural policies in Europe, in addition to trying to answer the initial question.